Solar Cells from Epitaxial Foils: An Epifoil Epiphany. (August 2015) - Govaerts, Jonathan; Trompoukis, Christos; Radhakrishnan, Hariharsudan S.; Tous, Loic; Granata, Stefano N.; Carnemolla, Enrico G.; Martini, Roberto; Marchegiani, Alessio; Karim, Marwa; Sharlandziev, Ivan; Bearda, Twan; Depauw, Valerie; et al.
Abstract: In this paper we want to share our efforts on how to translate our high-quality epitaxial foils (epifoils) into cell-level performance. After framing our motivation in the introduction, we elaborate our approach at imec using available background on this topic and expected challenges. After presenting our method, consisting of layout, buildup and processing sequence, we share and compare our findings, discuss our characterization methods and add some basic simulations to improve our understanding. In conclusion, we demonstrated how we could process epitaxial foils into cells, using a completely low-temperature process and keeping the foils attached to a carrier (parent wafer for the frontside, superstrate glass for the rear side) all the way through. Even though there is room for improvement on several aspects (both electrical and optical), in a first attempt this cell integration already resulted in a best open-circuit voltage (Voc) of 695 mV. Based on the loss analysis, the most promising improvements and their potential impact are pointed out.